Leptospira reservoirs among wildlife in Brazil: Beyond rodents - Fornazari, Felipe [UNESP]; Langoni, Helio [UNESP]; Marson, Pâmela Merlo [UNESP]; Nóbrega, Diego Borin; Teixeira, Carlos Roberto [UNESP] (Elsevier, 2018)
Leptospirosis is a disease of great importance in tropical regions. Infection occurs mainly through contact with water contaminated with the urine of infected animals, especially that of rodents. Despite the diversity and abundance of wild fauna in Brazil, little is known about the role of other wild species in the epidemiology of leptospirosis. This study aimed to investigate new reservoirs of Leptospira among wildlife in Brazil, using serological and molecular diagnoses in a large-sized sample. Biological samples were collected from 309 free-ranging mammals, belonging to 16 species. The majority of the animals included were opossums (Didelphis albiventris) and coatis (Nasua nasua). Blood and urine samples were subjected to the microscopic agglutination test (MAT) and real-time PCR, respectively. Genetic characterization of genomospecies was performed using PCR amplicons. Statistical analysis was applied to test associations between positive diagnoses and age, sex, season and type of environment. The prevalence of infection found via MAT and PCR was 11% and 5.5%, respectively. If these tests are taken to be complementary, the overall prevalence was 16%. The most common serogroups were Djasiman and Australis, while L. santarosai was the prevalent genomospecies. Significant differences in prevalence between animal species were observed. Greater risk of infection was detected among adult opossums than among young ones. The influence of each serogroup and genomospecies was tested for the same variables, and this revealed higher risk of infection by L. santarosai among male opossums than among females. The present study highlights the exposure and carrier status of several wild species in Brazil and it indicates that coatis and other carnivores are priorities for further investigations.
Keywords: Coati; Epidemiology; Leptospirosis; Opossum; Zoonosis